Egypt's Economic Potential. - Aliboni, Roberto (Routledge Library Editions: Egypt., 2012)
Over the last ten years the Egyptian economy has undergone a major transformation which has led to greater decentralisation and international competition. This transformation, along with changing circumstances in the surrounding Arab areas and the end of hostilities with Israel, has given a boost to the Egyptian economy. Without underestimating the obstacles that still stand in the way of sustained economic growth and development, this book foresees a more optimistic outlook for Egypt than do other such studies carried out by international organisations such as the World Bank. Egyp.